2005
DOI: 10.1002/jat.1004
|View full text |Cite
|
Sign up to set email alerts
|

Segmentary effects on the renal proximal tubule due to hexachloro‐1,3‐butadiene in rats: biomarkers related to gender

Abstract: Renal tissue biomarkers (glutamine synthetase and p-aminohippuric acid uptake) were studied in male and female rats after treatment with hexachloro-1,3-butadiene. Reduced glutathione content also was also determined in liver and kidney. Histopathological examination (light microscopy) was then performed. The aim was to define sex differences in nephrotoxic effects caused by the solvent injected i.p. at 50, 100 and 200 mg kg(-1) dose. The rats were sacrificed 24 and 48 h after treatment; after 24 h a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…36 Recently, Trevisan et al found that, unlike liver, kidney GSH content significantly increased 24 and 48 h after treatment with HCBD in male rats but not in female rats or in renal cortical slices, in vitro. 3 PSO is a rich source of conjugated fatty acids of which punicic acid is the most common. 37,38 Polyphenolic compounds are also present in the seed oil of the pomegranate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Recently, Trevisan et al found that, unlike liver, kidney GSH content significantly increased 24 and 48 h after treatment with HCBD in male rats but not in female rats or in renal cortical slices, in vitro. 3 PSO is a rich source of conjugated fatty acids of which punicic acid is the most common. 37,38 Polyphenolic compounds are also present in the seed oil of the pomegranate.…”
Section: Discussionmentioning
confidence: 99%
“…The solvent is also detected in aquatic organisms, birds, and mammals. 3 HCBD has deleterious health effects due to its toxicity and carcinogenicity. [4][5][6][7] HCBD is a potent nephrotoxin in rodents.…”
Section: Introductionmentioning
confidence: 99%
“…However, cyclacillin, which is a substrate of Pept1/PEPT1, was nephrotoxic in rats but not in monkeys, dogs, and humans; Pept1 is a brush-border transporter along the rat proximal tubule S1 and S2 segment, which may be expressed in higher abundance in M rats (see later) and may reabsorb the filtered compound to high, toxic levels [132,261,262]. Regarding nephrotoxicity of hexachlorobutadiene in rats, in one report, the damage in proximal tubules was stronger in M [20], whereas in another report, F were more sensitive [260]. The sensitivity of proximal tubules to toxic effects of acetaminophen, a drug that is secreted in proximal tubules via several Oats/OATs (reviewed in [39]), was much stronger in F, and this difference is lost in old animals, possibly due to age-dependent downregulation of the transporter [253].…”
Section: Gender Differences In Nephrotoxicitymentioning
confidence: 92%
“…The studies on sex-related nephrotoxicity of HCBD did not lead to unequivocal conclusions. Birner et al [43] found that HCBD-induced renal effects are more severe in male rats than in females in accordance with data on sex-specific sulfoxide metabolite formation, whereas other authors found that female rats were more sensitive to HCB [137][138][139][140] about four times than male rats [139]. These findings are probably in relation to differences in hepatic and renal enzymes responsible for the detoxification and/or activation of HCBD; in particular, female rat kidney shows marked dose-related decrease in nonprotein sulfhydryl content [137].…”
Section: Hexachloro-1:3-butadienementioning
confidence: 59%